2016
DOI: 10.1002/2015jd024245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amines on particle growth observed in new particle formation events

Abstract: Particle size distributions in the range of 0.01–10 µm were measured in urban Shanghai in the summer of 2013 using a Wide‐range Particle Spectrometer (WPS). Size‐segregated aerosol samples were collected concurrently using a Micro‐Orifice Uniform Deposit Impactor (MOUDI), which aided our in‐depth understanding of the new particle formation (NPF) mechanism in the polluted Yangtze River Delta area. During the observations, 16 NPF events occurred at high temperatures (~34.7°C) on clear and sunny days. In the ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 69 publications
4
57
4
Order By: Relevance
“…Numerous lab experiments and quantum chemical calculations reported amines play an important role in atmospheric nucleation and the growth of new particles (Zhang et al, 2012;Jen et 5 al., 2014;Chen et al, 2015aChen et al, , b, 2017Olenius et al, 2017), and oxalic acid, one of the most abundant dicarboxylic acids, was also proposed to be involved in NPF, and to be more readily bound to methylamine than to ammonia (Guo et al, 2016;Arquero et al, 2017;Hong et al, 2018). So far, it has been a challenge to accurately measure the mass concentrations of aminiums and oxalate in nucleation mode particles (Bzdek et al, 2013;Tao et al, 2016). During the sampling using the nano-MOUDI in this study, the bounce-off effect could be much large through a comparison between a rough estimation of mass concentration of 10 nanometer particles in three size bins of 10-56 nm using the number concentration measured by FMPS and the sum of ionic concentrations therein (not shown).…”
Section: The Roles Of Amines and Oxalic Acid In Growing New Particlesmentioning
confidence: 99%
“…Numerous lab experiments and quantum chemical calculations reported amines play an important role in atmospheric nucleation and the growth of new particles (Zhang et al, 2012;Jen et 5 al., 2014;Chen et al, 2015aChen et al, , b, 2017Olenius et al, 2017), and oxalic acid, one of the most abundant dicarboxylic acids, was also proposed to be involved in NPF, and to be more readily bound to methylamine than to ammonia (Guo et al, 2016;Arquero et al, 2017;Hong et al, 2018). So far, it has been a challenge to accurately measure the mass concentrations of aminiums and oxalate in nucleation mode particles (Bzdek et al, 2013;Tao et al, 2016). During the sampling using the nano-MOUDI in this study, the bounce-off effect could be much large through a comparison between a rough estimation of mass concentration of 10 nanometer particles in three size bins of 10-56 nm using the number concentration measured by FMPS and the sum of ionic concentrations therein (not shown).…”
Section: The Roles Of Amines and Oxalic Acid In Growing New Particlesmentioning
confidence: 99%
“…Recent work has shown that organic compounds may contribute considerably to particle nucleation (Ehn et al, 2014;Ortega et al, 2016;Tröstl et al, 2016;Willis et al, 2016). In particular, the need to measure and quantify gaseous atmospheric alkylamines has gained interest because of their exceptional ability to partake in atmospheric particle formation.…”
Section: Introductionmentioning
confidence: 99%
“…[81][82][83][84][85][86][87][88] Relevant to this, carboxylates and aminium ions have been shown to coexist in atmospheric particles. [89][90][91] We report here the results of studies of the uptake of gaseous n-butylamine on a series of solid diacids (C3-C8; HOOC(CH 2 ) n COOH, where n = 1-6) in a Knudsen cell at 296 AE 1 K. In addition to…”
Section: Introductionmentioning
confidence: 99%